Interfaith Marriage in the Human Rights Perspective and the Compilation of Islamic Law - Misbahul - Huda; Rahmat Dwi Putranto (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
Becoming a husband and wife via marriage is a sacred relationship shared by a woman and a man. Basically, marriage is governed by the laws of each religion. Interfaith marriage is one of the phenomenon that takes place in Indonesia. Some of these weddings were consummated in secret, but most of them were done so in public. Interfaith unions are likewise forbidden by Islam, according to Surah Al-Baqarah verse 221. Law Number 1 of 1974, article 2, also forbids interfaith unions. Interfaith weddings are still common in Indonesia, therefore this tradition has generated criticism even in the present day. Normative legal research is the methodology employed in this legal study. The findings of this study demonstrate that interfaith marriage is forbidden by the Compilation of Islamic Law (KHI) and Human Rights (HAM), which states that it is against God's mandates. All major religions forbid its adherents from marrying outside of their own faith. In order to compel all citizens to abide by the relevant legal regulations, the Marriage Law and the Compilation of Islamic Law both forbid interfaith marriages. The highest human right in terms of human rights is divinity, which means that all individuals are required to follow their god's laws. The primary issue under investigation is how Islamic law and human rights relate to interfaith marriage and the legal ramifications of the human rights perspective on such marriages, which forbids and does not accommodate interfaith unions because all of the freedoms and rights outlined in the declaration are subject to sharia, or Islamic law.